Elucidating intimate partner violence rate disparities between same- an opposite-sex couples: a demographic approach - Hubbell, James (Journal of interpersonal violence, 2024)
Studies on intimate partner violence (IPV) rates typically find higher rates for same-sex couples than opposite-sex couples. Regardless of sexual orientation, the risk for IPV perpetration is concentrated among young adults. Given that the HIV/AIDS epidemic significantly lowered the life expectancy of sexual minority men and that recent social movements have encouraged more youths to “come out,” population age differences may contribute to the observed differences in IPV rates between same- and opposite-sex couples. The present study applies direct age standardization and decomposition techniques to data from the National Incident-Based Reporting System and the American Community Survey to examine this possibility across 2,584 same-sex male, 4,029 same-sex female, and 284,614 opposite-sex physical IPV incidents. The results of the direct standardization procedures indicate physical IPV rates for same-sex male and same-sex female households would be 11.8% and 27.3% lower, respectively, if they had the same population age structure as opposite-sex households. The results of the decompositions indicate that differences in population age structure contribute 48% and 44% of the elevation in IPV rates in same-sex male and same-sex female households, respectively, compared to opposite-sex households. These findings demonstrate the promise of demographic methods to explain differences in offending rates between groups. These results suggest the need for prevention and intervention strategies aimed at youths. Future studies should be conducted with data on sexual orientation and gender identity to better elucidate the contribution of population age structure among various sexual and gender minority groups. Research comparing trends among sexual minority populations to the heterosexual population in particular should account for age where possible.